Combined Adsorption/Photocatalytic dye removal by copper-titania-fly ash composite - Kanakaraju, Devagi; Muhamad Hazim, Ya; Lim, Ying-Chin; Pace, Andrea (Elsevier Ltd., 2020)
Achieving both photocatalytic efficiency and adsorption capacity is essential to produce a highly efficient photocatalyst. This study fabricated a new photocatalyst by combining copper (Cu) doped titanium dioxide (TiO2) with fly ash (FA). The photocatalysts were synthesized using mild acid (acid-FA/Cu/TiO2), base (base-FA/ Cu/TiO2), and deionized water (rFA/Cu/TiO2) activated FA. EDX confirmed the inclusion of Cu in both Cu/TiO2 and FA/Cu/TiO2 composites. XRD analysis indicated the presence of the anatase form of TiO2 after Cu doping and incorporation into modified FA. All three FA/Cu/TiO2 composites demonstrated high absorption (UV and visible region) compared to their TiO2 and Cu/TiO2 counterparts based on the diffuse reflectance UV-Vis spectra. Complete removal of methyl orange under UV and 99.1% removal under visible light irradiation were attained using 1.5 g/L base-FA/Cu/TiO2. Both dark and irradiation phases demonstrated the synergistic role of adsorption TiO2 composites to ensure the removal of dye in water.